Napier Grass Derived Cellulose Acetate Membrane for Water Purification - Shrestha, Grisha; Kandel, Krishna; Aryal, Girja; Gautam, Prakash; Neupane, Bhanu Bhakta (Journal of Nepal Chemical Society, 2025)
Napier grass is one of the widely cultivated forage plants. The stem region of the plant, an agro waste, is being explored in fabrication of paper, biogas production, and as composite material. The purpose of this study was to extract cellulose from Napier grass, modification of the cellulose to cellulose acetate, and use the acetate in fabrication of membrane for filtration purpose. Cellulose was extracted from lignocellulosic biomass by drying, pulping followed by alkali treatment and bleaching to remove hemicellulose and lignin content from the biomass with the yield of 47%. The obtained cellulose was acetylated through reaction of acetic anhydride in the presence of iodine as catalyst and systematically compared with commercially available cellulose acetate. The yield of cellulose acetate was found to be 41.67%. The cellulose acetate membrane was fabricated using cellulose acetate using calcium carbonate nanoparticles as pore templates. The membrane was able to decrease turbidity from simulated water sample by 96%. This study suggested that the waste Napier grass stem could be used for efficient synthesis of cellulose acetate and fabrication of membrane for water purification.